The risk of serious bacterial infections among young ex-premature infants with fever - Yuval Barak-Corren; Yuval Barak-Corren; Yoav Elizur; Shira Yuval; Amalia Burstyn; Noy Deri; Shepard Schwartz; Orli Megged; Orli Megged; Orli Megged; Ori Toker; Ori Toker; et al. (Frontiers Media S.A., 2022)
Background and ObjectivesTo determine the rate of serious-bacterial-infections (SBI) in young ex-premature infants with fever, and to develop a risk-stratification algorithm for these patients.MethodsA retrospective cohort study including all infants who presented to the pediatric emergency department (ED) of a tertiary-care university-hospital between 2010 and 2020 with fever (≥38°C), were born prematurely (<37-weeks), had post-conception age of <52-weeks, and had available blood, urine, or CSF cultures. The rates of SBI by age-of-birth and age-at-visit were calculated and compared to a cohort of matched full-term controls.ResultsThe study included a total of 290 ex-premature cases and 290 full-term controls. There were 11 cases (3.8%) with an invasive bacterial infection (IBI) of either bacteremia, meningitis or both and only six controls (2.1%) with IBI (p = 0.32). Over 28-days chronologic-age, there were 10 (3.6%) IBIs among cases and no IBIs among the controls (p = 0.02). There were eight (3%) cases and three (1%) controls with IBI who were well-appearing on physical examination (p = 0.19). All eight well-appearing ex-premature infants were under 60-days adjusted-age, seven of whom (88%) were also under 28-days adjusted-age. There were 28 (10.6%) cases and 34 (12%) controls with urinary tract infection (UTI) (p = 0.5). Among cases under 60-days adjusted-age, urinalysis was not reliable to exclude UTI (50% negative).ConclusionsWell-appearing ex-preterm infants have a significant risk for IBI until the adjusted age of 28-days and for UTI until the adjusted age of 60-days. Further studies are needed to evaluate the approach to fever in this unique population.